The Short‐ and Medium‐Term Impacts of the Recession on the UK Income Distribution*. (4th June 2013) - Brewer, Mike; Browne, James; Hood, Andrew; Joyce, Robert; Sibieta, Luke
Abstract We study the short‐ and medium‐term impacts of the recent recession on the distribution of net household income in the UK. We document trends in the distribution of income during and immediately after the economy's 6.3 per cent contraction between 2008Q1 and 2009Q2. We then use a tax and benefit microsimulation model combined with macroeconomic and demographic forecasts to project the distribution of income up to 2015–16. As in other countries, immediate impacts of the recession on net household incomes are remarkably hard to detect, but the pain was merely delayed until 2010–11 and beyond. We find that the major difference between income groups is in the timing of the reductions in income, rather than in their magnitude. For those in the middle and upper parts of the distribution, dependent mainly on labour market income, falls in real income happened largely between 2009–10 and 2011–12. For those towards the bottom, dependent more on benefit incomes, falls in real income will happen largely as a result of the post‐recession fiscal tightening between 2010–11 and 2015–16. We explore the sensitivity of the results to different scenarios for employment and earnings: the central and qualitative conclusions prove robust.